Larval morphology of Paroster Sharp, 1882 (Coleoptera: Dytiscidae: Hydroporinae): reinforcement of the hypothesis of monophyletic origin and discussion of phenotypic accommodation to a hypogaeic environment - Alarie, Yves; Michat, Mariano C.; Watts, Chris H. S. (Zootaxa, 2009)
The larvae of 13 species (six epigaeic and seven hypogaeic) of the Australian endemic genus Paroster Sharp, 1882 are described with an emphasis on chaetotaxy of the head capsule, head appendages, legs, last abdominal segment and urogomphi. A cladistic analysis of 41 Hydroporinae species and 63 informative characters supports a monophyletic origin of members of Paroster, which share a labial palpus comprised of three palpomeres and the absence of the primary seta FE7. Contrary to their epigaeic counterparts, larvae of hypogaeic Paroster species have turned out to be very divergent morphologically. In addition to the common characteristics associated with hypogaeic living (i.e., absence of eye, reduced pigmentation, and thin or soft exoskeleton), larvae of these species have undergone a relative elongation/ enlargement of the head capsule and a more elongate and narrower mandible and have developed a variable number of secondary temporal spines. Compared to the other stygobitic species studied, larvae of Paroster hinzeae (Watts & Humphreys, 2001), P. macrosturtensis (Watts & Humphreys, 2006), P. stegastos (Watts & Humphreys, 2003) and P. darlotensis (Watts & Humphreys, 2003) evolved a disproportionately large head capsule relative to body size. Larvae of P. wedgeensis (Watts & Humphreys, 2003) and P. mesosturtensis (Watts & Humphreys, 2006) are deemed to have deviated the least from the hypothetical epigaeic Paroster groundplan.